2008
DOI: 10.1097/ijg.0b013e31815c3aeb
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Improper Scan Alignment on Retinal Nerve Fiber Layer Thickness Measurements Using Stratus Optical Coherence Tomograph

Abstract: Objective Misalignment of the Stratus optical coherence tomograph scan circle placed by the operator around the optic nerve head (ONH) during each retinal nerve fiber layer (RNFL) examination can affect the instrument reproducibility and its theoretical ability to detect true structural changes in the RNFL thickness over time. We evaluated the effect of scan circle placement on RNFL measurements. Design Observational clinical study. Methods Sixteen eyes of 8 normal participants were examined using the Stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 21 publications
5
62
0
Order By: Relevance
“…In contrast, the Stratus OCT requires the operator to choose the location of the circle, and previous studies have already shown that this procedure may affect RNFL thickness measurements. 32,33 Interestingly, we also confirmed that RNFL thickness measurements are slightly less repeatable in the nasal quadrant. This finding has already been reported with both TD-OCT and SD-OCT, 14 and, as previously suggested, may be related to the fact that the angle of incidence of the illuminating beam is such that the RNFL is dimmer nasally, so that the edges of the RNFL are less reliably identified.…”
Section: Discussionsupporting
confidence: 73%
“…In contrast, the Stratus OCT requires the operator to choose the location of the circle, and previous studies have already shown that this procedure may affect RNFL thickness measurements. 32,33 Interestingly, we also confirmed that RNFL thickness measurements are slightly less repeatable in the nasal quadrant. This finding has already been reported with both TD-OCT and SD-OCT, 14 and, as previously suggested, may be related to the fact that the angle of incidence of the illuminating beam is such that the RNFL is dimmer nasally, so that the edges of the RNFL are less reliably identified.…”
Section: Discussionsupporting
confidence: 73%
“…Although this wide range can be explained by individual characteristics, such as stage of disease and response to treatment, it is possible that non-centered scans and signal strength affected the ability to detect change. 63,64 Nonetheless, the wide individual variation should be considered when evaluating patients on a case-by-case basis. …”
Section: Octmentioning
confidence: 99%
“…[20][21][22] The effect of suboptimal scan centration, and alignment to the foveal axis is mostly on the distribution of thickness along the TSNIT plot, resulting in measures outside normal limits on sector and quadrant analysis. [23][24][25] A-scans are acquired through the optics of the eye; ocular magnification needs to be taken into account for scans in which thickness measures change significantly with distance from the optic nerve head rim margin. Specifically, in longer and myopic eyes, the scan path falls further from the rim margin where the nerve fiber thickness measures are less.…”
Section: Circumpapillary Retinal Nerve Fiber Layer Analysismentioning
confidence: 99%